Integrating Climate Change and Smart Agriculture Contents into Nigerian School Curriculum (Universitas Negeri Semarang, 2022)
The importance of the agricultural sector to the Nigerian economy is highly invaluable, although, it is highly responsive and vulnerable to climate change. Climate change has caused decline and volatility in agricultural production, thereby exacerbating food insecurity and hunger in countries such as Nigeria. Most of the Nigerian farmers are rainfed and conservative towards technological change, this calls for the need to develop curriculum contents on smart agriculture for youth who will steer agricultural activities in the nearest future. This study adopts Stufflebeam’s (Content-Input-Process-Product) curriculum content creation process to develop content on climate change and smart agriculture for incorporation into the senior school agricultural science curriculum in Nigeria. The contents were developed using the Food and Agricultural Organization of the United Nations outlined climate-smart agricultural practices as suggested in themes 1 and 2 of the curriculum Abstrak Sektor pertanian sangat penting bagi perekonomian Nigeria, meskipun sangat responsif dan rentan terhadap perubahan iklim. Perubahan iklim telah menyebabkan penurunan dan ketidakstabilan dalam produksi pertanian, sehingga memperburuk kerawanan pangan dan kelaparan di negara-negara seperti Nigeria. Sebagian besar petani Nigeria menggarap pertanian tadah hujan dan konservatif terhadap perubahan teknologi. Kondisi tersebut meniscayakan perlunya mengembangkan konten kurikulum pertanian cerdas (smart agriculture content) untuk pemuda yang akan mengarahkan kegiatan pertanian dalam waktu terdekat. Studi ini mengadopsi model Stufflebeam (Content-Input-Process-Product) dalam proses pembuatan konten kurikulum untuk mengembangkan materi tentang perubahan iklim dan pertanian cerdas untuk dimasukkan dalam kurikulum ilmu pertanian sekolah menengah di Nigeria. Konten dikembangkan mengacu pada Organisasi Pangan dan Pertanian Perserikatan Bangsa-Bangsa yang menguraikan praktik pertanian cerdas iklim sebagai tema 1 dan 2 yang disarankan dari kurikulum